Hp(3) response of the PHE PADC neutron personal dosemeter. (November 2017) - Tanner, Rick; Hager, Luke; Eakins, Jonathan; Gilvin, Phil
Abstract: Doses to the lens of the eye have long been recognized as one of the hazards of ionizing radiation, with a 150 mSv limit having been set for radiation protection purposes (ICRP, 1991), but more recent analysis of the epidemiology of cataract induction (Ainsbury et al., 2009) has led to the recommendation that the dose limit for exposures of the lens of the eye should be reduced to 20 mSv (ICRP, 2012). This has led to increased interest in doses to the lens of the eye and the control of those doses. Most focus of this interest has related to exposures from weakly penetrating radiation. However, H p (3) assessments will need to be entered in dose records, including an assessment of the neutron dose in mixed fields. The response of the PHE PADC neutron dosemeter is presented in terms of H p (10) and H p (3). These data show that the dosemeter response is closer to ideal in terms of H p (3) than it is in terms of H p (10) and that the dosemeter can be used for the assessment of H p (3). PHE will be ready for changes in UK legislation that are anticipated in 2018. Highlights: H p (3) conversion coefficients calculated for neutrons. H p (3) response of PHE neutron dosemeter determined. PHE neutron dosemeter shown to be appropriate for eye lens dosimetry in some circumstances without modification.